2020
DOI: 10.1016/j.archger.2020.104176
|View full text |Cite
|
Sign up to set email alerts
|

Interventions for reducing hospital-associated deconditioning: A systematic review and meta-analysis

Abstract: To determine the effectiveness of hospital-based interventions designed to reduce Hospital-Associated Deconditioning (HAD) for people in inpatient hospital settings.Materials & Methods: Systematic literature search of published and unpublished databases was conducted from (inception to 01 June 2020). Randomised and non-randomised controlled trials investigating the effectiveness of enhanced inpatient programmes aimed to reduce HAD in adults admitted to a hospital ward were included. Evidence was appraised usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 29 publications
1
16
0
1
Order By: Relevance
“…A recent meta-analysis focused on different interventions to reduce HAD. 114 The authors showed that enhanced inpatient programs reduced the risk of declining ADL ability by 4% at discharge, reduced nursing home residence by 8% at one to 3 months post-discharge and reduced 1-month mortality by 23%. However, the level of evidence remains low and it is important to design robust clinical trials with clear target populations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent meta-analysis focused on different interventions to reduce HAD. 114 The authors showed that enhanced inpatient programs reduced the risk of declining ADL ability by 4% at discharge, reduced nursing home residence by 8% at one to 3 months post-discharge and reduced 1-month mortality by 23%. However, the level of evidence remains low and it is important to design robust clinical trials with clear target populations.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding interventions, studies were scarce and highlighted the need for more research. A recent meta‐analysis focused on different interventions to reduce HAD 114 . The authors showed that enhanced inpatient programs reduced the risk of declining ADL ability by 4% at discharge, reduced nursing home residence by 8% at one to 3 months post‐discharge and reduced 1‐month mortality by 23%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Summary IV. A total of 20 references ( [10,33,53,90,[116][117][118][119][120][121][122][123][124][125][127][128][129][130]133,134]) were used to scope the following nutritional commonalities between hospital-associated vs. space-associated deconditioning/resilience. The significance of having an efficient food system that contributes to the maintenance of the individual's good nutritional status; the goal of reducing nutritional deficits and the intake of counterproductive substances; the importance of meal timing; the need to balance the musculoskeletal involution; the goal to avoid the recurrence of osteosarcopenia-related traumas.…”
Section: Nutritional Resilience In Astronautsmentioning
confidence: 99%
“…It is of paramount importance to overcome a pre-existing/hospital-derived osteosarcopenia, as it is known to be associated with poor outcome after surgery and increased risk of new fall-related traumas [120]. Undesirably, there remains uncertainty on how to defy this decay [121], and (with current knowledge) the further we move away from the peak of bone mass the more we are destined to fall.…”
mentioning
confidence: 99%